Dual-method molding of 4D shape memory polyimide ink - Xiao Li; Yangyang Yang; Yaoming Zhang; Tingmei Wang; Zenghui Yang; Qihua Wang; Xinrui Zhang (Materials & Design, 2020)
Thermoset shape memory polyimides (TPIs) are widely used in the fields of high-temperature smart devices. However, the recent molding of polyimides limits most of potentials in the form of two-dimensional film. In this work, we synthesized a novel shape memory polyimide (SMPI) ink that could be used for both Digital Light Process and extrusion molding 3D printing. Through UV-induced free radical polymerization, 3D custom polyimides ink can be cured rapidly. Remarkably, the 3D printed PI exhibits excellent shape memory performance, with Rf of 99.8%, Rr of 98.3%, therefore the 4D printing PI was successfully prepared. The 3D printed airplane, ultrasonic motor and pagoda can actively recover the film folding, expanding combined compressing, and vertical distorting to their permanent shape, which presents the outstanding 4D printing properties. Moreover, SMPI can be used in extrusion molding to print films, the residual stress induced the self-folding and then a vector model was applied to characterize transformation of extruded plates. In order to develop the application diversity of extruded 4D polyimide, self-folding box and stimuli-response gripper are designed, the gripper is able to pull up steel ball 15 times heavier than itself. Thus, SMPI will be benefit to expand the applied scope of SMPI.